Security Logics of Africa’s Divided Position on Russia’s Invasion of Ukraine (The Strategic Review for Southern Africa, 2022)
This article examines African states’ security interests concerning Russia in order to explain those states’ voting behaviour on a UN resolution condemning the invasion of Ukraine. African states do not form a bloc ready to support action taken by ‘the West’. Many African states are themselves authoritarian and harbour longstanding suspicion of European and North American powers. Russia has also built close security relations with many African governments as an arms supplier, provider of military assistance, and source of private military companies. Overall, African states may prefer to maintain relations with both Russia and its opponents rather than choosing between rival blocs.